Biophysics of lipid bilayers containing oxidatively modified phospholipids: insights from fluorescence and EPR experiments and from MD simulations - Jurkiewicz, Piotr; Olżyńska, Agnieszka; Cwiklik, Lukasz; Conte, Elena; Jungwirth, Pavel; Megli, Francesco M; Hof, Martin (Biochimica et biophysica acta, 2012)
This review focuses on the influence of oxidized phosphatidylcholines (oxPCs) on the biophysical properties of model membranes and is limited to fluorescence, EPR, and MD studies. OxPCs are divided into two classes: A) hydroxy- or hydroperoxy-dieonyl phospatidylcholines, B) phospatidylcholines with oxidized and truncated chains with either aldehyde or carboxylic group. It was shown that the presence of the investigated oxPCs in phospholipid model membranes may have the following consequences: 1) decrease of the lipid order, 2) lowering of phase transition temperatures, 3) lateral expansion and thinning of the bilayer, 4) alterations of bilayer hydration profiles, 5) increased lipid mobility, 6) augmented flip-flop, 7) influence on the lateral phase organisation, and 8) promotion of water defects and, under extreme conditions (i.e. high concentrations of class B oxPCs), disintegration of the bilayer. The effects of class A oxPCs appear to be more moderate than those observed or predicted for class B. Many of the abovementioned findings are related to the ability of the oxidized chains of certain oxPCs to reorient toward the water phase. Some of the effects appear to be moderated by the presence of cholesterol. Although those biophysical alternations are found at oxPC concentrations higher than the total oxPC concentrations found under physiological conditions, certain organelles may reach such elevated oxPC concentrations locally. It is a challenge for the future to correlate the biophysics of oxidized phospholipids to metabolic studies in order to define the significance of the findings presented herein for pathophysiology. This article is part of a Special Issue entitled: Oxidized phospholipids-their properties and interactions with proteins.
Keywords: Phospholipids; Electron Spin Resonance Spectroscopy; simulace molekulární dynamiky; fosfolipidy; Humans; Lipid Bilayers; Oxidation-Reduction; fluorescence; Fluorescence; elektronová paramagnetická rezonance; biofyzikální jevy; Biophysical Phenomena; lipidové dvojvrstvy; Molecular Dynamics Simulation; oxidace-redukce; lidé